2020
DOI: 10.1108/bfj-01-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of palm oil in water microemulsion for application in the food industry

Abstract: PurposeRed palm oil contains both tocopherol (∼30%) and tocotrienol (∼70%) with the latter having better antioxidant potency than the former by a factor of 60 times. The microemulsion is one of the most suitable carriers to protect this vitamin E from environmental stress due to food processing and storage. However, the instability of microemulsion might limit the presentation of vitamin E in the food industry. In the present study, we demonstrated the preparation of microemulsions from different ratios of pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The experimental results on these formulations demonstrated separations of the aqueous and organic phases. The results revealed that Span-60 played a significant role in the formulation's stability, which was validated by other studies also [23,24]. Although Tween-80 was used as a surfactant in four different formulations constituting the Span-60 (7-10 formulations) also, the prepared MEs seemed to be slightly cloudy, and their phases separated after 7 to 14 days.…”
Section: Formulation Of Optimal Microemulsion Carriersupporting
confidence: 75%
“…The experimental results on these formulations demonstrated separations of the aqueous and organic phases. The results revealed that Span-60 played a significant role in the formulation's stability, which was validated by other studies also [23,24]. Although Tween-80 was used as a surfactant in four different formulations constituting the Span-60 (7-10 formulations) also, the prepared MEs seemed to be slightly cloudy, and their phases separated after 7 to 14 days.…”
Section: Formulation Of Optimal Microemulsion Carriersupporting
confidence: 75%
“…The IR spectrum of HCT showed distinct peaks at 3413 cm −1 , which confirms the presence of -OH groups; aliphatic C-H stretching was observed at 2937 cm −1 as well as 2879 cm −1 , C=O was observed at 1706 cm −1 and 1640 cm −1 , -CH2 bending was seen at 1455 cm −1 , and, lastly, the spectrum showed C-O at 1078 cm −1 [42,60]. In the spectrum for the SMS-PCL blank, the peak observed at 2937 cm −1 is due to CH 2 vibrations, the peak at 1706 cm −1 is due to C=O vibrations, and the peak at 1611 cm −1 represents O-H vibrations, while the vibrations caused by CH 2 can be observed at the 1431 and 1390 cm −1 peaks, C-O and C-C stretching vibrations can be observed at 1264 cm −1 and 1196 cm −1 , respectively, and COO vibrations are shown at 1047 cm −1 [61,62].…”
Section: Chemical Evaluation Undertaken On the Sms-pcl Nanoparticles ...mentioning
confidence: 99%
“…The pump pushes the crude emulsion/pre-emulsion towards the available space between the forcer and homogenization sheet. The homogenizing pressure is typically between 50 and 200 MPa [56]. The pre-mix exits the space and colloids with the impact ring.…”
Section: High-energy Methodsmentioning
confidence: 99%